2016
DOI: 10.1167/iovs.15-18907
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Capillary Network and Foveal Avascular Zone in Eyes with Vein Occlusion and Fellow Eyes Analyzed With Optical Coherence Tomography Angiography

Abstract: Spectral-domain OCTA reveals abnormalities at different levels of perifoveolar retinal capillary network and is able to quantify the FAZ in RVO. Longitudinal studies may be considered to evaluate the clinical utility of OCTA in RVO and other retinal vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
118
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 28 publications
14
118
2
3
Order By: Relevance
“…This study also suggested that the findings in the DRL were more profound than those in the SRL in RVO subjects. Several other studies have also confirmed those findings (Rispoli, Savastano et al 2015, Adhi, Filho et al 2016) and are reviewed below. Interestingly, Kashani et al also demonstrated that some regions of intraretinal fluid could be visualized on OCTA in analogy to what Matsunaga et al showed for intraretinal fluid in DR (Kashani, Lee et al 2015).…”
Section: Review Of Clinical Studies Utilizing Octasupporting
confidence: 59%
See 1 more Smart Citation
“…This study also suggested that the findings in the DRL were more profound than those in the SRL in RVO subjects. Several other studies have also confirmed those findings (Rispoli, Savastano et al 2015, Adhi, Filho et al 2016) and are reviewed below. Interestingly, Kashani et al also demonstrated that some regions of intraretinal fluid could be visualized on OCTA in analogy to what Matsunaga et al showed for intraretinal fluid in DR (Kashani, Lee et al 2015).…”
Section: Review Of Clinical Studies Utilizing Octasupporting
confidence: 59%
“…Vascular tortuosity and collaterals were also subjectively noted in RVO subject eyes. The results of this paper seem to generalize to both 3×3 and 6×6-mm 2 fields, but a specific comparison of the two field sizes is lacking in the paper (Adhi, Filho et al 2016). …”
Section: Review Of Clinical Studies Utilizing Octamentioning
confidence: 79%
“…Despite being highly variable even in healthy subjects, 24 several conditions (e.g., DR, 25 retinal vein occlusion, 26 and sickle cell disease) 27 may affect the FAZ size due to the occlusion of capillaries surrounding the FAZ. As a result, the FAZ area in these patients is enlarged and more irregular and, thus, its manual quantification may not be straightforward, especially at the deep plexus.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] In addition, the OCTA has the potential to quantitatively analyze the retinal vessel density (VD) and the foveal avascular zone (FAZ) area. 26,27 Thus, OCTA has provided a better understanding of the relationship between the layerspecific retinal microvascular changes and the visual outcomes in patients with RVO. To date, several studies have reported the macular VD and FAZ before and after anti-VEGF therapy.…”
mentioning
confidence: 99%